Muhammad Abduh's Islamic Educational Thoughts And Its Relevance To Education In The Contemporary Era - M. Tajudin Zuhri; Rohmatulloh Rohmatulloh; Ijudin Ijudin; Masripah Masripah; Lalan Sahlani (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Muhammad Abduh was one of the leaders of the modernization of Islamic education. Muhammad Abduh's anxiety about the stagnation of Muslims made him excited and moved to modernize the Islamic education system to bring back the glory of Muslims. One of the things done by Muhammad Abduh was through reforming the Islamic education system and modernizing which was considered the most ideal step and effort in reforming the condition of Muslims at that time. This research attempts to unravel some of Muhammad Abduh's real thoughts and efforts in efforts to modernize and reform the Islamic education system and its relevance to contemporary-era education. By using the type of library research or literature. Muhammad Abduh's thoughts are very relevant to the world of contemporary education, i.e.: 1. Integration of general and religious knowledge in Islamic education, 2. Islamic education must cover all aspects which include cognitive, affective, and psychomotor, 3. Islamic education must activate students and emphasize students to have higher order thinking skills,4. Islamic education must pay attention to the psychological aspects of students Keywords: Muhammad Abduh, Islamic education, contemporary education.